Headache in Preeclampsia: Review Article - Mulia Dian Sumbawati; Hanik Badriyah Hidayati; Ernawati Ernawati (Universitas Airlangga, 2025)
Highlight: Headache in preeclampsia is classified as a type of secodary headache. Pregnant women with high blood pressure have a 17-fold increased risk of developing secondary headaches. Typical preeclampsia-related headaches are progressive, bilateral (frontal or occipital), throbbing, associated with visual abnormalities, getting worse with elevated blood pressure or exercise, and resistant to over-the-counter drugs.. ABSTRACT Preeclampsia is a multisystem vascular disease characterized by systemic disturbances in maternal endothelial function and symptoms such as arterial hypertension and organ dysfunction, including the kidneys, liver, and brain. A headache is defined as pain or discomfort localized in the head region. Pregnancy-related headaches may have primary causes, such as migraines, but they can also indicate potentially life-threatening secondary causes, including preeclampsia. Pregnant women with high blood pressure have a 17-fold increased risk of developing secondary headaches. Headaches associated with preeclampsia can adversely affect pregnancy and labor, increasing the risk of complications. Preeclampsia headaches can predict eclampsia or seizures 56% sensitivity and 83% specificity. According to research conducted in Indonesia, the majority of preeclampsia patients experienced severe headaches (65.2%), followed by moderate (19.6%), mild (13%), and no headaches (2.2%). Therefore, based on the existing literature, this article intends to compile scientific data on headache pain in preeclampsia patients.